Characteristics of Chemical Quality Reduction in Fresh Baung Fish (Mystus nemurus) with Different Methods of Death at Room Temperature. Issue 1 (March 2021) - Karnila, R.; Edison; Fadhlami, P. I.
Abstract: Baung fish is a fishery commodity that contains high water content so it is easy to decompose (high perisable product). The purpose of this study was (1) to examine the freshness level of the baung fish, (2) pH level, Total Volatile Base (TVB), and glycogen of the baung fish by different mortality death. This research was conducted using an experimental method, consisting of two steps: (1) preparation and observation of freshness level of fresh baungfish, (2) analysis of chemical reduction of fresh baungfish including pH, TVB, and glycogen content. The treatments of the research were (1) the baungfish died by itself (A1), (2) the fish were stabbed out the medulla oblongata (A2). Chemical reduction of fresh baung fish at room temperature was measured every 4 hours for 12 hours with parameters such as pH, TVB, and glycogen content. The data were analysed descriptively. The results of this research showed that the characteristics of fresh baung fish were move actively, healthy, difficult to catch, the opening and closing movements of the operculum were normal, and normal skin clour (not pale). The results of the chemical reduction test revealed that pH were 6.5 ± 0.05 at 0 hours to 7.0 ± 0.20 at 12 hours for treatment A1, while for treatment A2 was 6.3 ± 0.1 at 0 hours to 6, 6 ± 0.1 at 12 hours. The TVB test results showed 0.14 ± 0.04 at 0 hours to 31.32 ± 0.09 at 12 hours for A1 treatment. Whereas A2 treatment was 0.10 ± 0.03 at 0 hours to 26.30 ± 1.87 at 12 hours. Furthermore, glycogen levels showed at 6.67% ± 0.03 at 0 hours to 0.35% ± 0.13 at 12 hours for A1 treatment. While the A2 treatment was 7.69% ± 0.12 at 0 hours to 1.15% ± 0.26 at 12 hours.